Attentional Demands of Breathing Pattern Control and biochemical metabolic outcomes in Normal Subjects - Majid Ravanbakhsh; Mahyar Salavati; Behnam Akhbari; Esmaeil Ebrahimi; Babak Gousheh (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Normal breathing is essential for adjustment of natural metabolism of human body. Therefore, the aim of this study was to evaluate the control of breathing pattern in normal subjects both at rest and during cognitive loading. Materials & Methods: In this quasi-experimental study, 24 healthy subjects (14 males, 10 females) were selected by simple and convenient sampling. Spirometry data including inspiration and expiration times, total time of respiration, tidal volume, minute ventilation, respiratory rate, inspiratory-total time ratio, and capnography data containing end tidal CO2 were obtained from all participants in two conditions: with or without cognitive loading. Results: Mean of end tidal CO2 in expiration, inspiration times and total duration of respiration in rest condition was significantly larger than those of during cognitive loading. There was also a medium direct correlation between tidal volume, inspiration and expiration times, total duration of respiration and inspiratory-total time ratio and end tidal CO2. Conclusion: Cognitive loading has an inevitable effect on breathing pattern. There is also good correlation between breathing pattern and biochemical breathing of metabolic outcomes.